Effects of Shock Wave Phenomenon on Different Convergent Lengths in the Mixing Chamber of the Steam Ejector - Stefan Mardikus (International Journal of Applied Sciences and Smart Technologies, 2021)
The shock wave phenomenon is a phenomenon in a steam ejector that caused when the working fluid has high pressure, and suddenly it turns into low pressure and high speed. The shock wave effect will be investigated to the different convergent length in the mixing chamber to find the highest entrainment ratio as the performance of steam ejector. Operating pressure in the primary flow was in the range 0.68 MPa - 1.39 MPa, and the secondary flow was set 0.38 MPa to 0.65 MPa. The result of this study demonstrated that the highest entrainment ratio occurred in the convergent length of 69 mm.